Europeanization in VET Policy as a Process of Reshaping the Educational Space - Loogma, Krista (International Journal for Research in Vocational Education and Training, 2016)
The EU represents a transforming educational space, where national and supranational boundaries in educational governance are becoming blurred. The EU has become an important actor in educational governance and an important arena for policy learning and transfer. This paper explores how the process of reshaping the educational space manifests itself in the process of the Europeanization of VET policy in the case of Estonia. In Estonia, this process was followed by the growth of executive VET institutions and has developed from rather uncritical initial policy transfer to more active learning from the EU, although conformism can still be seen in cases of the introduction of standardizing policy tools.